A hybrid method towards automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2014)
In clinical work-up of breast cancer, nipple position is an important marker to locate lesions. Moreover, it serves as an effective landmark to register a 3D automated breast ultrasound (ABUS) images to other imaging modalities, e.g., X-ray mammography, tomosynthesis or magnetic resonance imaging (MRI). However, the presence of speckle noises caused by the interference waves and variant imaging directions poses challenges to automatically identify nipple positions. In this work, a hybrid fully automatic method to detect nipple positions in ABUS images is presented. The method extends the multi-scale Laplacian-based method that we proposed previously, by integrating a specially designed Hessian-based method to locate the shadow area beneath the nipple and areola. Subsequently, the likelihood maps of nipple positions generated by both methods are combined to build a joint-likelihood map, where the final nipple position is extracted. To validate the efficiency and robustness, the extended hybrid method was tested on 926 ABUS images, resulting in a distance error of 7.08±10.96 mm (mean±standard deviation).
EVALuna2:14367